2013
DOI: 10.1016/j.ultsonch.2012.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of activity of a commercial amylase under ultrasound-assisted irradiation

Abstract: The main objective of this work was to evaluate the effects of ultrasound irradiation on the activity of a commercial amylase. A central composite design was carried out to assess the effects of temperature and pH on the enzyme activity in the presence and absence of ultrasound irradiation. The activation energy, the influence of treatment time as well as the substrate concentration on enzyme activity were also determined in the presence and absence of ultrasound irradiation. The results demonstrated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…However, at 60°C, the enzyme activity was reduced by 17% in comparison with that of the nonultrasonicated enzyme. Similar change in amylase activity was observed when mixture of amylase preparation and starch was contemporarily ultrasonicated . In this study, when the ultrasonic power and time were fixed at 25 W/mL and 60 s, respectively, increase in operating temperature from 40°C to 60°C decreased the α‐amylase activity from 124 ± 0.5 to 87 ± 0.3 KU/mL.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…However, at 60°C, the enzyme activity was reduced by 17% in comparison with that of the nonultrasonicated enzyme. Similar change in amylase activity was observed when mixture of amylase preparation and starch was contemporarily ultrasonicated . In this study, when the ultrasonic power and time were fixed at 25 W/mL and 60 s, respectively, increase in operating temperature from 40°C to 60°C decreased the α‐amylase activity from 124 ± 0.5 to 87 ± 0.3 KU/mL.…”
Section: Resultssupporting
confidence: 78%
“…However, the yield of various enzymatic reactions in food and bioengineering was significantly enhanced under ultrasonic treatment . Among them, starch hydrolysis by amylases was reported to be improved when ultrasound was used in this biochemical operation . Starch hydrolysis has been performed in the production of beer, bakery products, maltodextrin, maltose, glucose, and high fructose syrup .…”
Section: Introductionmentioning
confidence: 99%
“…It can be noticed a gap in the literature regarding the use of ultrasound to increase peroxidase activity, but the results of this study are similar to those found for other enzymes, such as Souza et al 16 who evaluated the commercial enzyme amylase activity under the irradiation of ultrasound. For this, they used a design of experiments to evaluate the exposure temperature and pH in relation to enzymatic activity in the presence and absence of ultrasonic irradiation.…”
Section: Resultssupporting
confidence: 84%
“…However, it is expected that this increase in the activity occurs only for short period [11]. In previous works, we have also verified significant modifications in the effects of process variables, namely temperature, pH, solid to liquid ratio and enzyme load using ultrasound [12,20,21].…”
Section: Resultssupporting
confidence: 68%